2018
DOI: 10.1111/bjh.15721
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic haematopoietic cell transplantation impacts on outcomes of mantle cell lymphoma with TP53 alterations

Abstract: Summary TP53 alterations portend extremely poor prognosis in patients with mantle cell lymphoma treated with standard treatment modalities. We reviewed outcomes of 42 patients with available TP53 status who had received a reduced‐intensity or non‐myeloablative allogeneic haematopoietic cell transplant at our institution. We demonstrated a 2‐year overall survival and progression‐free survival of 78% [95% confidence interval (CI) 60–88] and 61% (95% CI 43–75), respectively. The 2‐year cumulative incidences of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 15 publications
0
29
1
Order By: Relevance
“…Allogenic SCT —This modality can be useful in high‐risk, transplant‐eligible TP53 ‐mutated relapsed MCL. Allo‐SCT can provide long term disease control in 30% of MCL patients …”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…Allogenic SCT —This modality can be useful in high‐risk, transplant‐eligible TP53 ‐mutated relapsed MCL. Allo‐SCT can provide long term disease control in 30% of MCL patients …”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…TP53 alterations were previously associated with a poor prognosis in MCL patients treated with standard treatment modalities 44,45 . A recent study suggested that allogeneic hematopoietic cell transplantation may be a beneficial treatment option for patients with TP53 mutations 46 . For the younger MCL patients receiving cytarabine-containing chemotherapy and autologous stem cell transplantation, Ferrero et al 9 developed the MIPI-genetic index (MIPI-g), which is a prognostic model integrating MIPI-c prognostic index with genetic data (TP53, and KMT2D mutations).…”
Section: Discussionmentioning
confidence: 99%
“…[ 68 69 70 71 79 80 ] Young, physically fit patients with a Mantle Cell Lymphoma International Prognostic Index high-risk score with or without TP53 mutations or blastoid/pleomorphic variants can be considered for allogeneic SCT. [ 81 82 ] Finally, for patients unfit for treatment, oral corticosteroids and alkylating agents can be offered for symptom relief. Palliative radiotherapy can be offered to patients with compromised vital organs or for pain relief.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%